Kajian Psikologi Tokoh Utama Kinan dalam Novel “Layangan Putus” Karya Mommy Asf - Susilawati Susilawati; Ari Diana (Jurnal Riset Rumpun Ilmu Bahasa, 2024)
This study aims to describe the psychological elements of the character Kinan based on the id, ego and superego in the novel Layangan Putus by Mommy asf, to describe the form of psychological problems in the character Kinan in the novel Layangan Putus by Mommy Asf, and to describe the form of conflict defense mechanisms in the character Kinan in the novel Layangan Putus by Mommy Asf. The research used a qualitative approach. While the method used is the content analysis method. The source of funds in this study is the text of the novel Layangan Putus by Mommy Asf published by RDM Publisher in 2020, the first printing. The data collection technique is a written documentation technique. The data analysis technique is a qualitative descriptive technique. The findings of this study are as follows: (1) Psychological elements of the Kinan character were found based on the id, ego and superego, namely there is an uncomfortable id, a pain id and an unfulfilled need id, there is an angry ego in the Kinan character and there is that there a high personal standard superego, (2) It was found were 5 psychological problems in the Kinan character, including: mood disorders based on subjective feelings consisting of feelings of sadness, anger and disappointment, there were anxiety disorders, stress disorders, somatoform disorders and personality disorders including: adventitious, borderline, obsessive-compulsive, histrionic and narcissistic.